« Nous n’avons jamais été “soutenables” : pourquoi revisiter aujourd’hui la notion de durabilité forte ? » - Jacques Theys; Clémence Guimont (Développement Durable et Territoires)
In an interview realized with Clémence Guimont in August 2018 Jacques Theys notices the procedural approach's failure of sustainable development. He argues for a return to strong sustainability which is the recognition of absolute limits to actions but circumscribed to major risks and to critical breakdown for future generations. He clarifies the consequences for relationship with nature which are irreducible to functions. He also establishes connexions with a substantive approach of sustainable development. Then, he describes the history of strong sustainability. He highlights to what extent this strong approach has been represented or not in the past public policies and in prospective studies. He questions about the possibilities which could make this approach acceptable in our actual context.